The Effect of Halal Certification on SME Competitiveness Through Consumer Trust - Faisal Amri; Ayi Muhiban; Sumarsid; Siluh Putu Sri Dia Utari (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: In the contemporary dynamics of the Islamic market, halal certification has transcended its theological roots to become a strategic instrument determining the economic viability of MSMEs, thus this study aims to dissect the influence of halal certification on business competitiveness by positioning consumer trust as a mediating mechanism. Methods: Utilizing a causal-explanatory quantitative approach, primary data were gathered from 150 respondents in the Banten region through purposive sampling and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The empirical analysis demonstrates that halal certification significantly contributes to fostering consumer trust while simultaneously accelerating MSME competitiveness, where the most critical finding confirms the role of consumer trust as a mediator that bridges the gap between legal compliance and market performance. Conclusion and suggestion: This underlines that while halal certification serves as a quality signal to reduce information asymmetry, its effectiveness in driving competitive advantage is heavily contingent upon how well that signal is internalized as a trust asset by the consumer. Consequently, the study suggests that the synergy between regulatory compliance and reputation management is a fundamental strategy for MSMEs to achieve sustainable business scalability within the halal economic ecosystem.